(untitled) (Nigerian Journal of Technology, 2021)
The use of computers to conduct examinations is more effective than traditional paper-based examinations in terms of immediate availability of results and long term cost effectiveness. This however is faced with identifying and authenticating the real identities of the examinees so as to reduce impersonation. The study examined the existing authentication method available on the Computer-based test system of Air Force Institute of Technology (AFIT), Kaduna, Nigeria and proposed the fingerprint biometric technique as an additional method to authenticate the examinees. The fingerprint biometric authentication was developed using FlexCode SDK and implemented on DigitalPersona 4500 fingerprint reader – the recommended scanner by JAMB for fingerprint enrollment. The system was developed using PHP scripting language on XAMPP local server and MySQL database system. The results obtained showed that there is no need for a middleware to link the authentication module with the CBT because of the Single Sign-On technique implemented. This result thus improved the level of authentication and access to the CBT. This will therefore reduce impersonation and increase the level of awareness of CBT by academic stakeholders. http://dx.doi.org/10.4314/njt.v40i2.14